Collective Infrastructures of Care: Ollas Comunes Defying Food Insecurity During the COVID-19 Pandemic. (May 2022) - Desmaison, Belén; Jaime, Kelly; Córdova, Paola; Alarcón, Lia; Gallardo, Luciana
The COVID-19 pandemic highlighted the importance of solidarity and care networks in withstanding crises. One example is the emergence of Ollas Comunes (Common Pots, a type of community kitchen) in the peripheries of Lima, which highlighted the enormous need for spaces that promote, channel, and strengthen collective support. Consolidating these networks, and allowing them to prosper over time, constitutes an alternative aimed at improving the living conditions of marginal groups, a crucial task in reducing urban inequalities. Co-production occurred at multiple scales: from local implementations of community kitchens to the design of urban networks for agriculture, water and sanitation, and food production. Collective innovation happened in technical terms towards promoting the efficient use of renewable resources (extending the concept of care to the care of the territory and the environment) and in the formulation of alternative governance in the maintenance and repair of the implemented infrastructure towards a renewed sense of citizenship.